Pelatihan Komitmen Organisasi bagi Kader Aisyiyah Pimpinan Ranting Aisyiyah Kedungwuluh Lor, Kecamatan Patikraja: Organizational Commitment Training for Aisyiyah Cadres of the Kedungwuluh Lor Aisyiyah Branch Leadership, Patikraja District - Endratno, Hermin; Fauzan, Akhmad; Rakhmawati, Fitri (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Science and Technology for Community Organizational Development (IbM PP) program aims to enhance organizational commitment among Aisyiyah cadres from the Aisyiyah Branch Leadership (PRA) in Kedungwuluh Lor, Patikraja District, through training in cadre development strategies. The activities will cover organizational commitment, communication between individuals/teams, and collaboration among members of the PRA in Kedungwuluh Lor, Patikraja District. This training is crucial because, in general, organizational commitment, communication, and cooperation among Aisyiyah members still need improvement to strengthen the organization. The current problem is the suboptimal communication and collaboration between Aisyiyah members, who are generally in their 40s. Therefore, lectures, discussions, and training related to organizational commitment, communication, and cooperation among members are necessary. The learning process uses experiential learning, a method that focuses on and centers on the participants' own experiences and knowledge. After participating in this outreach activity, participants demonstrated an increased understanding of organizational commitment. This was evident in their enthusiasm for the discussion and Q&A. In addition, participants also gave a positive response to the material presented and stated that they would try to increase their commitment to Aisyiyah.